Dimensi pembentuk kesadaran identitas keacehan dan citra diri Aceh - M. Nazaruddin (Masyarakat, Kebudayaan dan Politik, 2014)
Constructing Dimension of Acehnese Identity was understood as social-historical aspect that has been shaping self-image and self-realization for Aceh people. The dynamic of Aceh People struggle was based on identity realization and world's view as Aceh people. Aceh is widely known by inherent Islamic Identity since the beginning of Hijriyah year. Research conducted by holding interview and literature review. This study aims to bring back the realization of identity and self-image of Aceh people. Aceh people hold to their Islamic identity tightly and use it as a considerable dimension to design their identity development socially and politically. This identity was implemented in social action, social institution, and social value orientation to preserve the Islamic value in Aceh. Self-image in this context was understood as value orientation, social, cultural, political, and economic system with Islamic value and rites was widely understood.